2020
DOI: 10.1021/jacs.0c04288
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of the Odd–Even Effect of Macroscopic Properties of n-Alkanethiolate Self-Assembled Monolayers: Bulk or Interface?

Abstract: Elucidating the influence of the monolayer interface versus bulk on the macroscopic properties (e.g., surface hydrophobicity, charge transport, and electron transfer) of organic self-assembled monolayers (SAMs) chemically anchored to metal surfaces is a challenge. This article reports the characterization of prototypical SAMs of n-alkanethiolates on gold (CH3(CH2)nSAu, n = 6-19) at the macroscopic scale by electrochemical impedance spectroscopy and contact angle goniometry, and at the molecular level, by infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 84 publications
8
46
0
Order By: Relevance
“…The second and third reactions involve, respectively, the gain or loss of an electron by the thiyl radical. We calculated the energy required to form the anion RS − ( ) from RS • and an electron on Au (equations [1] and [2]): [4] = + where is the work function of the Au(hkl) surface, and is the electronic affinity of the radical in vacuum, calculated as (−2.71 eV). Lastly, the cation formation, draining --…”
Section: Rs-au → Rs • + Au (Surf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The second and third reactions involve, respectively, the gain or loss of an electron by the thiyl radical. We calculated the energy required to form the anion RS − ( ) from RS • and an electron on Au (equations [1] and [2]): [4] = + where is the work function of the Au(hkl) surface, and is the electronic affinity of the radical in vacuum, calculated as (−2.71 eV). Lastly, the cation formation, draining --…”
Section: Rs-au → Rs • + Au (Surf)mentioning
confidence: 99%
“…Moreover, it has been observed a renewed interest in fundamental research about thiolate-SAMs. For instance, the molecular origin of the odd-even effects 4 and whether a dipolar group modifies the electron-tunneling across SAMs 5 have been recently studied. The interest has been mainly triggered due to the wide range of applications of thiolate-SAMs in molecular electronic devices.…”
mentioning
confidence: 99%
“…The spectral features at 1550 and 1483 cm –1 are the asymmetric (ν a (COO – )) and symmetric (ν s (COO – )) stretching vibrations of COO – , respectively. We observed that the carboxylate peaks near 1483 cm –1 appear in C12, 14, and 16 SAMs, but not in the C11 SAM, which may be related to the odd–even effect and will be further studied in future work.…”
Section: Resultsmentioning
confidence: 85%
“…The odd−even effect on macroscopic dimensions of formed nanoparticles arises primarily from a difference in the chemical composition at the interfaces and is related to the terminal group orientation as previously described for self-assembled monolayers (SAMs). 18 The surface hydrophobicity originates from changes in the polyethylene chain orientation as n odd presents a "methyl-like" surface, exhibiting higher contact angles (greater surface hydrophobicity) than n even of comparable chain length, exposing an "ethyl-like" surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%